Aluminum plastic film and lithium ion battery

By using a nylon layer, an aluminum foil layer and a CPP support layer in the aluminum plastic film, and a passivation layer, a polyurethane glue layer and a diisocyanate film layer are provided on the aluminum foil layer, the problem of corrosion of aluminum plastic film in the electrolyte is solved. It achieves higher adhesion and electrolyte corrosion resistance, extending the service life of the battery.

CN222473587UActive Publication Date: 2025-02-14HUIZHOU WANJI NEW ENERGY MATERIALS CO LTD

Patent Information

Application Number
CN202421219526.4
Authority / Receiving Office
CN · China
Patent Type
Utility models(China)
Current Assignee / Owner
Filing Date
2024-05-30
Publication Date
2025-02-14
Estimated Expiration
2034-05-30

AI Technical Summary

Technical Problem

The existing aluminum-plastic films are prone to corrosion when contacting the electrolyte, resulting in a reduction or failure of the bonding strength between the aluminum foil layer and the CPP layer, affecting the service life of the battery.

Method used

A nylon layer, an aluminum foil layer and a CPP support layer are laminated in sequence, and a passivation layer, a polyurethane glue layer and a diisocyanate film layer are provided on the matte and shiny structure of the aluminum foil layer to enhance adhesion and resistance to electrolyte corrosion. performance.

Benefits of technology

By enhancing the adhesion between the aluminum foil layer and the CPP layer and the electrolyte corrosion resistance, the service life of the battery is extended and the heat resistance of the aluminum-plastic film is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN222473587U_ABST
    Figure CN222473587U_ABST
Patent Text Reader

Abstract

The utility model provides an aluminum plastic film and a lithium ion battery. The aluminum plastic film comprises a nylon layer, an aluminum foil layer and a CPP supporting layer which are stacked in sequence. The aluminum plastic film further comprises a passivation layer, a polyurethane adhesive layer and a diisocyanate film layer. A matt surface structure and a bright surface structure are formed on two surfaces of the aluminum foil layer. The passivation layer comprises a first acrylate film layer and a second acrylate film layer, one surface of the first acrylate film layer is adhered to the matt surface structure, and one surface of the second acrylate film layer is adhered to the bright surface structure. One surface of the polyurethane adhesive layer is adhered to the other surface of the first acrylate film layer, and the other surface of the polyurethane adhesive layer is adhered to the nylon layer. One surface of the diisocyanate film layer is adhered to the second acrylate film layer, and one surface of the diisocyanate film layer is adhered to the CPP supporting layer. Wherein the thickness of the first acrylate film layer and the thickness of the second acrylate film layer are both 0.1-0.3 [mu] m.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of batteries, and in particular to an aluminum-plastic film and a lithium-ion battery. Background Art

[0002] Aluminum-plastic film is usually in direct contact with highly corrosive electrolyte. Once the aluminum-plastic film is not corrosion-resistant, problems such as aluminum foil perforation, leakage and short circuit will occur, which will greatly affect the service life of the battery. At present, aluminum-plastic film generally includes nylon layer, aluminum foil layer and CPP layer (electrolyte-resistant layer, mainly made of polypropylene), and the layers are compounded by adhesives.

[0003] However, judging from the organic solvent composition of the electrolyte, it is mainly carbonate solvents. According to the principle of like dissolves like, the currently commonly used adhesives are easily corroded by the electrolyte, which reduces or fails the bonding strength between the aluminum foil layer and the CPP layer, that is, the peel strength between the aluminum foil layer and the CPP layer is low, which makes the aluminum-plastic film lose its packaging protection effect on the battery, such as patent CN213150884U.

[0004] Therefore, there is an urgent need for an aluminum-plastic film that is resistant to electrolyte corrosion and has high peel strength. Utility Model Content

[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and provide an aluminum-plastic film and a lithium-ion battery that are resistant to electrolyte corrosion and have high peel strength.

[0006] The purpose of this disclosure is achieved through the following technical solutions:

[0007] An aluminum-plastic film comprises a nylon layer, an aluminum foil layer and a CPP support layer stacked in sequence;

[0008] The aluminum-plastic film also includes a passivation layer, a polyurethane adhesive layer and a diisocyanate film layer;

[0009] The two sides of the aluminum foil layer are formed with a matte surface structure and a bright surface structure;

[0010] The passivation layer comprises a first acrylate film layer and a second acrylate film layer, one side of the first acrylate film layer is bonded to the matte surface structure, and one side of the second acrylate film layer is bonded to the bright surface structure;

[0011] One side of the polyurethane adhesive layer is bonded to the other side of the first acrylic film layer, and the other side of the polyurethane adhesive layer is bonded to the nylon layer;

[0012] One side of the diisocyanate film layer is bonded to the second acrylate film layer, and one side of the diisocyanate film layer is bonded to the CPP support layer;

[0013] Wherein, the thickness of the first acrylate film layer and the second acrylate film layer are both 0.1 μm-0.3 μm.

[0014] In one embodiment, the CPP supporting layer includes a CPP laminating layer, a CPP core layer and a CPP heat-sealing layer, one side of the CPP laminating layer is bonded to one side of the diisocyanate film layer, the other side of the CPP laminating layer is bonded to one side of the CPP core layer, and the CPP heat-sealing layer is bonded to the other side of the CPP core layer.

[0015] In one embodiment, the thickness of the CPP laminating layer accounts for 5% to 15% of the thickness of the CPP supporting layer;

[0016] The thickness of the CPP core layer accounts for 70% to 80% of the thickness of the CPP support layer;

[0017] The thickness of the CPP heat-sealing layer accounts for 15% to 25% of the thickness of the CPP supporting layer.

[0018] In one of the embodiments, the thickness of the CPP support layer is 30 μm, 40 μm, 45 μm, 50 μm, 75 μm or 80 μm.

[0019] In one embodiment, the nylon layer is a polyamide film layer;

[0020] The thickness of the nylon layer is 15 μm to 30 μm.

[0021] In one embodiment, the aluminum foil layer is a 8021 aluminum alloy foil layer or a 8079 aluminum alloy foil layer;.

[0022] In one embodiment, the thickness of the aluminum foil layer is 30 μm-60 μm.

[0023] In one embodiment, the thickness of the polyurethane adhesive layer is 2 μm-6 μm.

[0024] In one embodiment, the thickness of the diisocyanate film layer is 0.5 μm-2 μm.

[0025] A lithium ion battery comprises the aluminum-plastic film described in any one of the above embodiments.

[0026] Compared with the prior art, the present invention has at least the following advantages:

[0027] 1. By providing a first acrylate film layer and a second acrylate film layer on the matte surface structure and the bright surface structure of the aluminum foil layer, and the thickness of the first acrylate film layer and the second acrylate film layer is between 0.1μm and 0.3μm, it is possible to prevent oxidation corrosion of the surface of the aluminum foil layer by the internal and external environment, and then the polyurethane adhesive layer is used to strengthen the bonding force between the nylon layer and the aluminum foil layer, so that moisture and oxygen can be prevented from invading the interior of the battery cell, so that the aluminum-plastic film plays a protective role on the battery cell.

[0028] 2. By arranging the diisocyanate film layer between the second acrylate film layer and the CPP support layer, the diisocyanate reacts with the maleic anhydride and the dianhydride on the CPP support layer to generate an imide ring and a polyimide with higher heat resistance, and then the diisocyanate reacts with the acrylate on the second acrylate film layer to cure. On the one hand, the bonding effect between the second acrylate film layer, the diisocyanate film layer and the CPP support layer can be improved, the peel strength between the CPP support layer and the aluminum foil layer can be enhanced, and the electrolyte corrosion resistance of the aluminum-plastic film can be improved. On the other hand, the heat resistance of the diisocyanate film layer is enhanced through the reaction, and the heat resistance of the aluminum-plastic film is improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the technical solutions of the embodiments of the present disclosure, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present disclosure and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.

[0030] Figure 1 This is a schematic diagram of the structure of an aluminum-plastic film in one embodiment;

[0031] Figure 2 This is a real picture of the aluminum-plastic film being wound;

[0032] Figure 3 This is a real picture of the aluminum-plastic film when it is laid flat;

[0033] Figure 4 This is a real picture of the aluminum-plastic film with the nylon layer peeled off;

[0034] Figure 5 This is a real picture of the CPP support layer of the aluminum-plastic film being peeled off. DETAILED DESCRIPTION

[0035] In order to facilitate the understanding of the present disclosure, the present disclosure will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present disclosure are given in the drawings. However, the present disclosure can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present disclosure more thoroughly and comprehensively understood.

[0036] It should be noted that when an element is referred to as being "fixed to" another element, it may be directly on the other element or there may be a central element. When an element is considered to be "connected to" another element, it may be directly connected to the other element or there may be a central element at the same time. The terms "vertical", "horizontal", "left", "right" and similar expressions used herein are for illustrative purposes only and do not represent the only implementation method.

[0037] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present disclosure. The terms used herein in the specification of the present disclosure are only for the purpose of describing specific embodiments and are not intended to limit the present disclosure. The term "and / or" used herein includes any and all combinations of one or more related listed items.

[0038] The present disclosure provides an aluminum-plastic film including a nylon layer, an aluminum foil layer and a CPP support layer stacked in sequence. The aluminum-plastic film also includes a passivation layer, a polyurethane adhesive layer and a diisocyanate film layer. Matt surface structure and bright surface structure are formed on both sides of the aluminum foil layer. The passivation layer includes a first acrylate film layer and a second acrylate film layer, one side of the first acrylate film layer is bonded to the matte surface structure, and one side of the second acrylate film layer is bonded to the bright surface structure. One side of the polyurethane adhesive layer is bonded to the other side of the first acrylate film layer, and the other side of the polyurethane adhesive layer is bonded to the nylon layer. One side of the diisocyanate film layer is bonded to the second acrylate film layer, and one side of the diisocyanate film layer is bonded to the CPP support layer. Wherein, the thickness of the first acrylate film layer and the second acrylate film layer is 0.1μm-0.3μm.

[0039] See also Figure 1 In order to better understand the aluminum-plastic film 10 of the present disclosure, the aluminum-plastic film 10 is further explained below:

[0040] The aluminum-plastic film 10 of one embodiment includes a nylon layer 100, an aluminum foil layer 200 and a CPP support layer 300 stacked in sequence. The aluminum-plastic film 10 also includes a passivation layer 400, a polyurethane adhesive layer 500 and a diisocyanate film layer 600. Matt surface structure 210 and bright surface structure 220 are formed on both sides of the aluminum foil layer 200. The passivation layer 400 includes a first acrylate film layer 410 and a second acrylate film layer 420, one side of the first acrylate film layer 410 is bonded to the matte surface structure 210, and one side of the second acrylate film layer 420 is bonded to the bright surface structure 220. One side of the polyurethane adhesive layer 500 is bonded to the other side of the first acrylate film layer 410, and the other side of the polyurethane adhesive layer 500 is bonded to the nylon layer 100. One side of the diisocyanate film layer 600 is bonded to the second acrylate film layer 420, and one side of the diisocyanate film layer 600 is bonded to the CPP support layer 300. The thickness of the first acrylate film layer 410 and the second acrylate film layer 420 are both 0.1 μm-0.3 μm.

[0041] In this embodiment, by providing a first acrylate film layer 410 and a second acrylate film layer 420 on the matte surface structure 210 and the bright surface structure 220 of the aluminum foil layer 200, and the thickness of the first acrylate film layer 410 and the second acrylate film layer 420 is between 0.1 μm and 0.3 μm, it is possible to prevent oxidation corrosion of the surface of the aluminum foil layer 200 by the internal and external environment, and then the polyurethane adhesive layer 500 is used to strengthen the bonding force between the nylon layer 100 and the aluminum foil layer 200, so that moisture and oxygen can be prevented from invading the interior of the battery cell, so that the aluminum-plastic film 10 plays a protective role on the battery cell.

[0042] Furthermore, by arranging the diisocyanate film layer 600 between the second acrylate film layer 420 and the CPP support layer 300, the diisocyanate reacts with the maleic anhydride and the dianhydride on the CPP support layer 300 to generate an imide ring and a polyimide with higher heat resistance, and then the diisocyanate reacts with the acrylate on the second acrylate film layer 420 to be cured. On the one hand, the bonding effect between the second acrylate film layer 420, the diisocyanate film layer 600 and the CPP support layer 300 can be improved, the peel strength between the CPP support layer 300 and the aluminum foil layer 200 is enhanced, and the performance of the aluminum-plastic film 10 against electrolyte corrosion is improved. On the other hand, the heat resistance of the diisocyanate film layer 600 is enhanced through the reaction, and the heat resistance of the aluminum-plastic film 10 is improved.

[0043] It should be noted that the first acrylate film layer 410 and the second acrylate film layer 420 are passivation layers formed by treating the matte surface structure 210 and the bright surface structure 220 on the surface of the aluminum foil layer 200 with a trivalent chromium passivator containing acrylate, which can prevent the oxidation corrosion of the surface of the aluminum foil layer 200 by the internal and external environments. By reacting the diisocyanate with the maleic anhydride and the dianhydride on the CPP support layer 300 to generate an imide ring and a polyimide with high heat resistance, and then curing the diisocyanate with the acrylate on the second acrylate film layer 420, a film layer with strong bonding force, high heat resistance and electrolyte corrosion resistance is formed between the CPP support layer 300 and the second acrylate film layer 420, and the peel strength between the CPP support layer 300 and the aluminum foil layer 200 is improved, thereby effectively improving the protective performance of the aluminum-plastic film 10.

[0044] Furthermore, the CPP support layer 300 is formed by cooling and solidifying the hot CPP cast on the second acrylate film layer 420. The second acrylate film layer 420 is a passivation layer formed by treating the bright surface structure 220 of the aluminum foil layer 200 with a trivalent chromium passivator containing acrylate, wherein acrylate refers to an adhesive substance prepared by copolymerizing carboxyl-containing acrylate monomers with unsaturated olefin monomers and adding an appropriate amount of additives. After the second acrylate film layer 420 contacts diisocyanate, it also undergoes a curing reaction under the action of heat provided by the cast hot CPP, thereby obtaining a film layer with strong adhesiveness. The film layer can enhance the peel strength between the aluminum foil layer 200 and the CPP support layer 300, thereby preventing the electrolyte inside the lithium-ion battery from electrochemically corroding the aluminum foil layer 200.

[0045] It should be noted that the passivator is not limited to the trivalent chromium passivator of acrylate, and can be other passivators containing acrylate. The above-mentioned materials, passivators and passivation methods are all prior arts and are not within the protection scope of the present disclosure.

[0046] like Figure 1As shown, in one embodiment, the CPP support layer 300 includes a CPP laminating layer 310, a CPP core layer 320 and a CPP heat-sealing layer 330. One side of the CPP laminating layer 310 is bonded to one side of the diisocyanate film layer 600, the other side of the CPP laminating layer 310 is bonded to one side of the CPP core layer 320, and the CPP heat-sealing layer 330 is bonded to the other side of the CPP core layer 320. It should be noted that the material of the CPP laminating layer 310 is composed of homopolymer polypropylene or random copolymer polypropylene resin or a mixture thereof, and the total molecular weight of the polymer obtained by polymerization is 150,000 to 300,000. The polymer component contains maleic anhydride modified polypropylene, which can react with diisocyanate to solidify and achieve close bonding with the second acrylate film layer 420 of the aluminum foil layer 200. The material of the CPP core layer 320 is a blend of polyolefin elastomer, metallocene polyethylene and homopolymer polypropylene, and the melting point of the polymer formed thereby is between 155°C and 165°C, and the total molecular weight is between 150,000 and 300,000, so that the CPP core layer 320 has good rigidity and electrolyte corrosion resistance. The material of the CPP heat seal layer 330 is a blend of terpolymer polypropylene, polyolefin elastomer, and random copolymer polypropylene molecular chains by adding ethylene monomers to the molecular chains, and the melting point of the polymer formed thereby is between 135°C and 145°C, so that the CPP heat seal layer 330 has good heat seal performance and improves the impact resistance of the CPP heat seal layer 330.

[0047] It should be noted that three layers of CPP are extruded through an extrusion device, namely, a CPP laminating layer 310, a CPP core layer 320 and a CPP heat sealing layer 330, and then cooled and solidified. The above-mentioned method for forming the CPP support layer 300 and the material of the three layers of CPP are both prior arts and are not within the scope of protection of the present disclosure.

[0048] like Figure 1 As shown, in one embodiment, the thickness of the CPP laminating layer 310 accounts for 5% to 15% of the thickness of the CPP supporting layer 300. The thickness of the CPP core layer 320 accounts for 70% to 80% of the thickness of the CPP supporting layer 300. The thickness of the CPP heat sealing layer 330 accounts for 15% to 25% of the thickness of the CPP supporting layer 300. It should be noted that the thickness of the CPP laminating layer 310 between 5% and 15% can well combine the aluminum foil layer 200 and the CPP supporting layer 300, thereby improving the peel strength of the aluminum foil layer 200 and the CPP supporting layer 300. The thickness of the CPP core layer 320 between 70% and 80% can well improve the rigidity of the CPP supporting layer 300 and enhance the electrolyte corrosion resistance of the CPP supporting layer 300. The thickness of the CPP heat-sealing layer 330 is between 15% and 25%, which enables the CPP support layer 300 to have better heat-sealing performance and improves the impact resistance of the CPP support layer 300.

[0049] like Figure 1 As shown, in one embodiment, the thickness of the CPP support layer 300 is 30 μm, 40 μm, 45 μm, 50 μm, 75 μm or 80 μm. It is understandable that the thickness of the CPP support layer 300 is adjusted according to the size of the battery cell and the concentration of the electrolyte to ensure that the aluminum-plastic film 10 has better protection performance.

[0050] like Figure 1 As shown, in one embodiment, the nylon layer 100 is a polyamide film layer. The thickness of the nylon layer 100 is 15 μm to 30 μm. It is understandable that the thickness of the nylon layer 100 between 15 μm and 30 μm can well protect the aluminum foil layer 200, reduce scratches and dirt on the outer surface of the aluminum-plastic film 10, and ensure that the lithium-ion battery has a good appearance.

[0051] like Figure 1 As shown, in one embodiment, the aluminum foil layer 200 is an aluminum alloy foil layer of type 8021 or an aluminum alloy foil layer of type 8079. It should be noted that the aluminum foil layer 200 is an aluminum alloy foil layer of type 8021 or an aluminum alloy foil layer of type 8079.

[0052] like Figure 1 As shown, in one embodiment, the thickness of the aluminum foil layer 200 is 30 μm-60 μm. The matte surface and the bright surface are distinguished according to the difference in metal brightness between the two surfaces of the aluminum foil layer 200. The thickness of the aluminum foil layer 200 between 30 μm-60 μm can prevent moisture and oxygen from invading the interior of the battery cell.

[0053] like Figure 1 As shown, in one embodiment, the thickness of the polyurethane adhesive layer 500 is 2 μm-6 μm. It should be noted that the thickness of the polyurethane adhesive layer 500 between 2 μm and 6 μm can well bond the nylon layer 100 and the first acrylic film layer 410 .

[0054] It should be noted that the polyurethane adhesive is bonded between the nylon layer 100 and the first acrylic film layer 410 through a chemical reaction, thereby forming a polyurethane adhesive layer 500 , which improves the bonding force between the nylon layer 100 and the aluminum foil layer 200 .

[0055] like Figure 1As shown, in one embodiment, the thickness of the diisocyanate film layer 600 is 0.5 μm-2 μm. It should be noted that the thickness of the diisocyanate film layer 600 is between 0.5 μm and 2 μm, which can make the diisocyanate react with the maleic anhydride and the dianhydride on the CPP support layer 300 to generate an imide ring and a polyimide with higher heat resistance, and then the diisocyanate reacts with the acrylate on the second acrylate film layer 420 to solidify. On the one hand, it can improve the bonding effect between the second acrylate film layer 420, the diisocyanate film layer 600 and the CPP support layer 300, enhance the peel strength between the CPP support layer 300 and the aluminum foil layer 200, and enhance the electrolyte corrosion resistance of the aluminum-plastic film 10. On the other hand, the heat resistance of the diisocyanate film layer 600 is enhanced through the reaction, and the heat resistance of the aluminum-plastic film 10 is improved, thereby effectively improving the stability and safety of the lithium-ion battery.

[0056] It should be noted that the chemical materials mentioned above are all existing technology materials and can be purchased on the market. They are not within the scope of protection of this disclosure. This disclosure only protects the connection relationship between the layers, which meets the requirements for object protection of utility models.

[0057] Further, in order to verify the authenticity of the aluminum-plastic film disclosed herein, Figures 2 to 5 It can be known that the aluminum-plastic film disclosed in the present invention is real.

[0058] The present disclosure also provides a lithium-ion battery, comprising the aluminum-plastic film described in any of the above embodiments.

[0059] In this embodiment, by providing a first acrylate film layer and a second acrylate film layer on the matte surface structure and the bright surface structure of the aluminum foil layer, and the thickness of the first acrylate film layer and the second acrylate film layer is between 0.1μm and 0.3μm, it is possible to prevent oxidation corrosion of the surface of the aluminum foil layer by the internal and external environments, and then the polyurethane adhesive layer is used to strengthen the bonding force between the nylon layer and the aluminum foil layer, thereby preventing moisture and oxygen from invading the interior of the battery cell, so that the aluminum-plastic film plays a protective role on the battery cell.

[0060] Furthermore, by arranging the diisocyanate film layer between the second acrylate film layer and the CPP support layer, the diisocyanate reacts with the maleic anhydride and the dianhydride on the CPP support layer to generate an imide ring and a polyimide with higher heat resistance, and then the diisocyanate reacts with the acrylate on the second acrylate film layer to cure. On the one hand, the bonding effect between the second acrylate film layer, the diisocyanate film layer and the CPP support layer can be improved, the peel strength between the CPP support layer and the aluminum foil layer can be enhanced, and the electrolyte corrosion resistance of the aluminum-plastic film can be improved. On the other hand, the heat resistance of the diisocyanate film layer is enhanced through the reaction, and the heat resistance of the aluminum-plastic film is improved, thereby effectively improving the stability and safety of the lithium-ion battery.

[0061] Examples are listed below, but it should be noted that the following examples do not exhaust all possible situations, and the materials used in the following examples can be obtained from commercial channels unless otherwise specified.

[0062] Example 1

[0063] Step A: performing surface passivation treatment on an aluminum foil with a thickness of 40 μm, so that the aluminum foil layer is not only corrosion-resistant, but also forms an acrylic film layer on both sides thereof;

[0064] Step B: using polyurethane adhesive to laminate the matte aluminum foil and nylon (25 μm), aging at 70° C. for 6 days to produce a semi-finished product;

[0065] Step C: Apply a layer of diisocyanate film on the bright surface of the semi-finished product by micro-concave reverse coating, and the glue amount is controlled within the range of 1.0g / m 2 ;

[0066] Step D: The semi-finished product is pulled onto a cooling roller, and the temperature of the cooling roller is controlled at about 40°C;

[0067] Step E: using a three-layer co-extrusion device to extrude three layers of CPP, setting the temperature at 200°C to extrude the adhesive layer, the core layer, and the heat-sealing layer in sequence, with the thickness ratio of the three layers being 10%: 70%: 20%; the total thickness of the three-layer CPP is controlled at 45 μm;

[0068] Step F: wherein the laminating layer first contacts the aluminum foil diisocyanate film layer, then the core layer, and finally the heat sealing layer;

[0069] Step G: Further, the semi-finished product is pulled to the composite roller by the guide roller, pressed by the electromagnetic roller, the rubber roller and the rubber roller back roller, continuously cooled and rolled up to obtain an aluminum-plastic film with a thickness of 115 μm.

[0070] Example 2

[0071] Step A: performing surface passivation treatment on an aluminum foil having a thickness of 55 μm, so that the aluminum foil is not only corrosion-resistant, but also forms an acrylic film layer on both sides thereof;

[0072] Step B: using polyurethane adhesive to laminate the matte aluminum foil and nylon (25 μm), aging at 70° C. for 6 days to produce a semi-finished product;

[0073] Step C: Apply a layer of diisocyanate film on the bright surface of the semi-finished product by micro-concave reverse coating, and the glue amount is controlled within the range of 1.0g / m2;

[0074] Step D: The semi-finished product is pulled onto a cooling roller, and the temperature of the cooling roller is controlled at about 40°C;

[0075] Step E: Use a three-layer co-extrusion device to extrude three layers of CPP, set the temperature to 200°C, extrude the adhesive layer, the core layer, and the heat-sealing layer in sequence, and the thickness ratio of the three layers is 10%: 70%: 20%; the total thickness of the three-layer CPP is controlled at 30μm;

[0076] Step F: wherein the laminating layer first contacts the aluminum foil diisocyanate film layer, then the core layer, and finally the heat sealing layer;

[0077] Step G: Further, the semi-finished product is pulled to the composite roller by the guide roller, pressed by the electromagnetic roller, the rubber roller and the rubber roller back roller, continuously cooled and rolled up to obtain an aluminum-plastic film with a thickness of 115 μm.

[0078] Example 3

[0079] Step A: performing surface passivation treatment on an aluminum foil having a thickness of 45 μm, so that the aluminum foil is not only corrosion-resistant, but also forms an acrylic film layer on both sides thereof;

[0080] Step B: using polyurethane adhesive to laminate the matte aluminum foil and nylon (25 μm), aging at 70° C. for 6 days to produce a semi-finished product;

[0081] Step C: Apply a layer of diisocyanate film on the bright surface of the semi-finished product by micro-concave reverse coating, and the glue amount is controlled within the range of 1.0g / m2;

[0082] Step D: The semi-finished product is pulled onto a cooling roller, and the temperature of the cooling roller is controlled at about 40°C;

[0083] Step E: Use a three-layer co-extrusion device to extrude three layers of CPP, set the temperature to 200°C, extrude the adhesive layer, the core layer, and the heat-sealing layer in sequence, and the thickness ratio of the three layers is 10%: 70%: 20%; the total thickness of the three-layer CPP is controlled at 40μm;

[0084] Step F: wherein the laminating layer first contacts the aluminum foil diisocyanate film layer, then the core layer, and finally the heat sealing layer;

[0085] Furthermore, the semi-finished product is pulled to the composite roller by the guide roller, pressed by the electromagnetic roller, the rubber roller and the rubber roller back roller, continuously cooled and rolled up to obtain an aluminum-plastic film with a thickness of 115 μm.

[0086] Comparative Example 1

[0087] 113μm thick aluminum-plastic film produced by traditional technology

[0088] The aluminum-plastic films of Examples 1-3 and Comparative Example 1 were subjected to the following tests:

[0089] Peel force test: Cut a long strip sample with a length greater than 150 mm and a width of (15±0.1) mm, and use a tensile testing machine to test it. The initial distance between the clamps is (100±5) mm. The test is carried out at a speed of (100±10) mm / min, and the peel value between the aluminum foil layer and the CPP layer is recorded.

[0090] Electrolyte resistance test: Cut a long strip sample with a length greater than 150 mm and a width of (15±0.1) mm, heat seal it in an electrolyte bag, place the sample in an 85°C environment for 3D, take it out, clean it, dry it, and then perform a peel strength test. The test results are shown in Table 1.

[0091] Table 1

[0092] sample Stripping value without electrolyte immersion Stripping value after immersion in electrolyte Comparative Example 1 12N 8N Example 1 Unable to peel off Unable to peel off Example 2 Unable to peel off Unable to peel off Example 3 Unable to peel off Unable to peel off

[0093] It can be seen from Table 1 that the bonding strength between the aluminum foil layer and the CPP support layer in the aluminum-plastic film disclosed in the present invention is relatively large, and the film has good resistance to electrolyte corrosion.

[0094] Compared with the prior art, the present invention has at least the following advantages:

[0095] 1. By forming the first acrylate film layer and the second acrylate film layer on the surface of the aluminum foil layer, the oxidation corrosion of the aluminum foil surface by the internal and external environment can be prevented, and the adhesion between the nylon layer and the aluminum foil layer is strengthened by the polyurethane adhesive layer, so as to prevent moisture and oxygen from invading the interior of the battery cell, so that the aluminum-plastic film can protect the battery cell.

[0096] 2. By arranging the diisocyanate film layer between the second acrylate film layer and the CPP support layer, the diisocyanate reacts with the maleic anhydride and the dianhydride on the CPP support layer to generate an imide ring and a polyimide with higher heat resistance, and then the diisocyanate reacts with the acrylate on the second acrylate film layer to cure. On the one hand, the bonding effect between the second acrylate film layer, the diisocyanate film layer and the CPP support layer can be improved, the peel strength between the CPP support layer and the aluminum foil layer can be enhanced, and the electrolyte corrosion resistance of the aluminum-plastic film can be improved. On the other hand, the heat resistance of the diisocyanate film layer is enhanced through the reaction, and the heat resistance of the aluminum-plastic film is improved.

[0097] The above-mentioned embodiments only express several implementation methods of the present disclosure, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the disclosed patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present disclosure, and these all belong to the protection scope of the present disclosure. Therefore, the protection scope of the disclosed patent shall be subject to the attached claims.

Claims

1. An aluminum-plastic film, comprising a nylon layer, an aluminum foil layer and a CPP support layer stacked in sequence, characterized in that: The aluminum-plastic film also includes a passivation layer, a polyurethane adhesive layer and a diisocyanate film layer; The two sides of the aluminum foil layer are formed with a matte surface structure and a bright surface structure; The passivation layer comprises a first acrylate film layer and a second acrylate film layer, one side of the first acrylate film layer is bonded to the matte surface structure, and one side of the second acrylate film layer is bonded to the bright surface structure; One side of the polyurethane adhesive layer is bonded to the other side of the first acrylic film layer, and the other side of the polyurethane adhesive layer is bonded to the nylon layer; One side of the diisocyanate film layer is bonded to the second acrylate film layer, and one side of the diisocyanate film layer is bonded to the CPP support layer; Wherein, the thickness of the first acrylate film layer and the second acrylate film layer are both 0.1 μm-0.3 μm.

2. The aluminum-plastic film according to claim 1, characterized in that: The CPP supporting layer comprises a CPP laminating layer, a CPP core layer and a CPP heat sealing layer, one side of the CPP laminating layer is bonded to one side of the diisocyanate film layer, the other side of the CPP laminating layer is bonded to one side of the CPP core layer, and the CPP heat sealing layer is bonded to the other side of the CPP core layer.

3. The aluminum-plastic film according to claim 2, characterized in that: The thickness of the CPP laminating layer accounts for 5% to 15% of the thickness of the CPP supporting layer; The thickness of the CPP core layer accounts for 70% to 80% of the thickness of the CPP support layer; The thickness of the CPP heat-sealing layer accounts for 15% to 25% of the thickness of the CPP supporting layer.

4. The aluminum-plastic film according to claim 3, characterized in that: The thickness of the CPP support layer is 30 μm, 40 μm, 45 μm, 50 μm, 75 μm or 80 μm.

5. The aluminum-plastic film according to claim 1, characterized in that: The nylon layer is a polyamide film layer; The thickness of the nylon layer is 15 μm to 30 μm.

6. The aluminum-plastic film according to claim 1, characterized in that: The aluminum foil layer is a 8021 aluminum alloy foil layer or a 8079 aluminum alloy foil layer.

7. The aluminum-plastic film according to claim 1, characterized in that: The thickness of the aluminum foil layer is 30 μm-60 μm.

8. The aluminum-plastic film according to claim 1, characterized in that: The thickness of the polyurethane adhesive layer is 2 μm-6 μm.

9. The aluminum-plastic film according to claim 1, characterized in that: The thickness of the diisocyanate film layer is 0.5 μm-2 μm.

10. A lithium ion battery, characterized in that: The invention comprises the aluminum-plastic film according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Aluminum-plastic film structure and lithium ion battery

    CN213150884U

Cited By

  • Aluminum-plastic film for battery, preparation method of aluminum-plastic film, battery and electric device

    CN121546239A